Direction and Desire: Culture Sector Research for the Next Decade - Luka, Mary Elizabeth; Sokoloski, Robin (Culture and Local Governance / Culture et gouvernance locale, 2023)
In this contribution, Research in Residence (RinR) co-facilitators Mary Elizabeth Luka and Robin Sokolsoki host a conversation with members of the RinR Funder Advisory, addressing the dynamics of collaboration, impact assessment, and applied research in the Canadian culture sector, using RinR as a case in point. While projects and operational approaches that incorporate partnerships and collaboration have been encouraged and funded for many decades through programs such as the Digital Strategy Fund at the Canada Council for the Arts, or by the Social Sciences and Research Council of Canada through its suite of partnership grants, how funders collaborate or enable partnerships among themselves or more directly with sector organizations has been less supported or evident. Additionally, over the last decade, industry and scholarly researchers have repeatedly noted that the sector tends to depend on a narrow band of research practices to conduct impact assessments— primarily from financial or economic points of view—and thereby to inform future directions not just for the organizations but also for the sector. To respond to this situation, in 2020, Mass Culture convened a series of discussions that resulted in various levels of resource support as well as participation commitments from several funder organizations for what became the Research-in-Residence: Arts’ Civic Impact initiative in 2021-23. This article traces the snowball effect of bringing various levels of funders onboard for this project before turning to discussions of how the group worked together throughout the project, including key learnings shared across the funding ecosystem and into the sector.